179k views
2 votes
Simplify.(x-3)(x^2-4x-7)

User Ozzah
by
5.1k points

2 Answers

5 votes

Hello there,

Simplify.(x-3)(x^2-4x-7)

Quick Answer: x^3-7x^2+5x+21



User Viktor Bardakov
by
5.8k points
7 votes

Answer:

x^3-7x^2+5x+21

Explanation:

To simplify the expression, apply the distributive property. The distributive property states to multiply each term in each parenthesis.

x*x^2=x^3

x*-4x=-4x^2

x*-7=-7x

-3*x^2=-3x^2

-3*-4x=12x

-3*-7=21

This gives the expression x^3-4x^2-7x-3x^2+12x+21. Combine like terms and get x^3-7x^2+5x+21.

User AmITheRWord
by
5.1k points